Apelin as a marker for monitoring the tumor vessel normalization window during antiangiogenic therapy. Issue 1 (12th November 2015) - Zhang, Li; Takara, Kazuhiro; Yamakawa, Daishi; Kidoya, Hiroyasu; Takakura, Nobuyuki
Abstract : Antiangiogenic agents transiently normalize tumor vessel structure and improve vessel function, thereby providing a window of opportunity for enhancing the efficacy of chemotherapy or radiotherapy. Currently, there are no reliable predictors or markers reflecting this vessel normalization window during antiangiogenic therapy. Apelin, the expression of which is regulated by hypoxia, and which has well‐described roles in tumor progression, is an easily measured secreted protein. Here, we show that apelin can be used as a marker for the vessel normalization window during antiangiogenic therapy. Mice bearing s.c. tumors resulting from inoculation of the colon adenocarcinoma cell line HT29 were treated with a single injection of bevacizumab, a mAb neutralizing vascular endothelial growth factor. Tumor growth, vessel density, pericyte coverage, tumor hypoxia, and small molecule delivery were determined at four different times after treatment with bevacizumab (days 1, 3, 5, and 8). Tumor growth and vessel density were significantly reduced after bevacizumab treatment, which also significantly increased tumor vessel maturity, and improved tumor hypoxia and small molecule delivery between days 3 and 5. These effects abated by day 8, suggesting that a time window for vessel normalization was opened between days 3 and 5 during bevacizumab treatment in this model. Apelin mRNA expression and plasma apelin levels decreased transiently at day 5 post‐treatment, coinciding with vessel normalization. Thus, apelin is a potential indicator of the vessel normalization window during antiangiogenic therapy. Abstract : Recently it has become widely accepted that angiogenesis inhibitors transiently normalize immature blood vessels in the tumor, improving perfusion and thus delivery of anti‐cancer agents to the tumor. However, the normalization window indicating the optimal time to administer anti‐cancer drugs most effectively is thus‐far difficult to determine, especially by peripheral blood monitoring methods. Here, we provide evidence that apelin, a ligand for APJ expressed on endothelial cells, is a candidate molecule for monitoring the time window of tumor vascular normalization.